Carbon Storage in Coffee Agroforestry Systems: Role of Native and Introduced Shade Trees in the Central Peruvian Amazon - Noelito Salgado Veramendi; Lorena Estefani Romero-Chavez; Eldhy Sianina Huerto Pajuelo; Carolina del Carmen Ibarra Porras; Joseph Michael Cunyas-Camayo; Uriel Aldava Pardave; Geomar Vallejos-Torres; Richard Solórzano Acosta (Agriculture, 2025)
What is the potential impact on carbon storage of the native and introduced tree species commonly associated with coffee in the central Peruvian Amazon? Coffee is a pivotal crop within the Peruvian economy. Nevertheless, the establishment of new plantations—driven by the subsistence needs of smallholder farmers—has led to expansion into forested areas. Given the significance of this crop and the demonstrated ecosystem benefits of agroforestry systems (AFSs), the aim of this study was to evaluate the influence of native and introduced shade tree species on carbon storage in coffee plantations. This study was observational and exhibited characteristics of an unbalanced incomplete block design. Agroforestry systems (AFSs) with shade tree species such as Inga, Retrophyllum rospigliosii, Eucalyptus and Pinus, and three unshaded coffee plantations, were included in this study. The total carbon stored in each AFS was higher than in unshaded coffee plantations. Soil contributed between 47% and 91% to total carbon storage, shade trees (24–46%), coffee (2–7%), leaf litter (0.6–1.9%) and shrubs and herbaceous plants (0.02–0.3%). The AFS with R. rospigliosii achieved the highest carbon storage with 190.38 Mg ha−1, highlighting the compatibility of this species with coffee plantations, as well as its positive effect on climate change mitigation in deforested areas.